Electrode and preparation method thereof, electrochemical device and electronic device
By adjusting the distribution of polymer compounds in the active material layer through thermogravimetric analysis in the electrode of the electrochemical device, the problem of increasing the electrode thickness affecting the performance of the electrochemical device is solved, and the energy density of the electrochemical device is improved.
Patent Information
- Application Number
- CN202180031527.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-11-15
AI Technical Summary
In existing electrochemical devices, an increase in electrode thickness will affect the performance of the electrochemical device, resulting in the inability to significantly increase the energy density of the electrochemical device.
By performing thermogravimetric analysis under an inert atmosphere, the distribution of polymer compound in the active material layer is adjusted so that the content of polymer compound is reduced in the thickness direction, and the conductivity of the active material layer is improved, thereby increasing the thickness of the electrode to increase the energy density of the electrochemical device.
The thickness of the electrode and the energy density of the electrochemical device are improved, while the performance of the electrochemical device is maintained, and the problem of deterioration of conductivity caused by excessive thickness of the active material layer is avoided.
Smart Images

Figure CN115552658B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrodes and preparation methods thereof, electrochemical devices and electronic devices. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, have the advantages of high energy density, high power, and long cycle life, and are widely used in various fields. With the development of technology, the requirements for the energy density of electrochemical devices are getting higher and higher. In order to improve the energy density of electrochemical devices, some technologies increase the capacity or voltage of active materials, and other technologies increase the content of active materials per unit volume and reduce the content of inactive materials. The proportion of inactive substances can be reduced by reducing the thickness of the current collector or the separator, reducing the proportion of inactive materials in the formula, and preparing thicker electrodes. However, in actual application, the thickness of the current collector and the separator has been reduced to near the limit, so the electrode thickness can only be increased. However, excessive increase in the thickness of the electrode may affect the performance of the electrochemical device, so the thickness of the electrode cannot be significantly increased. Therefore, how to increase the thickness of the electrode as much as possible to increase the capacity of the electrochemical device while ensuring the performance of the electrochemical device is an urgent problem to be solved. Summary of the invention
[0003] Some embodiments of the present application provide an electrode and a preparation method thereof, an electrochemical device and an electronic device, wherein a thermogravimetric analysis is performed on a detection area at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the mass percentage of weight loss in the detection area from 200°C to 800°C gradually increases as the spacing distance between the detection area and the current collector in the thickness direction decreases, thereby improving the conductivity of the active material layer, which is beneficial to increase the thickness of the active material layer to improve the energy density of the electrochemical device.
[0004] In some embodiments of the present application, an electrode is proposed, which includes a current collector and an active material layer located on one side or both sides of the current collector; along the thickness direction of the active material layer, the active material layer is divided into 4 parts, each part is a detection area, and the detection area is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis show that the mass percentage of weight loss in the detection area from 200°C to 800°C gradually increases with the decrease in the spacing distance between the detection area and the current collector in the thickness direction, which is beneficial to improving the kinetic properties of the active material layer, and further beneficial to increasing the thickness of the electrode to increase the capacity and energy density of the electrochemical device.
[0005] In some embodiments of the present application, a thermogravimetric analysis is performed on the active material layer at a heating rate of 10°C / min under an inert atmosphere, and the result of the thermogravimetric analysis shows that the number of weight loss peaks of the active material layer at 200°C to 800°C is greater than or equal to 2. This indicates that the active material layer in the embodiments of the present application contains at least two polymer substances.
[0006] In some embodiments of the present application, the number of weight loss peaks of the active material layer at 200°C to 350°C is greater than or equal to 1, and the number of weight loss peaks of the active material layer at 350°C to 800°C is greater than or equal to 1. This indicates that the embodiments of the present application simultaneously have polymer compounds with different decomposition temperatures.
[0007] In some embodiments of the present application, the weight loss mass percentage of the active material layer at 200° C. to 350° C. is M 1 , 0≤M 1 ≤2.2%, in some embodiments, 0.1≤M 1 In some embodiments, the weight loss mass percentage of the active material layer at 350°C to 800°C is M 2 , 0≤M 2 ≤13%, in some embodiments, 0.15≤M 2 ≤3.4%.
[0008] In some embodiments of the present application, the electrode is a negative electrode. In some embodiments, the compaction density of the active material layer is ρ ≥ 0.6 g / cm 3 ; A higher compaction density is beneficial to increasing the energy that can be stored per unit volume of the electrochemical device. In some embodiments, the thickness of the active material layer on one side of the current collector h ≥ 13 μm, and a thicker thickness is beneficial to carrying more active materials, thereby improving the energy density of the electrochemical device. In some embodiments, the porosity n of the active material layer satisfies: 35% ≥ n ≥ 30%. Too small a porosity will lead to insufficient electrolyte infiltration, and too large a porosity will lead to a decrease in energy density. In some embodiments, the active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon-based materials, tin-based materials, lithium metal materials or carbon materials. In some embodiments, the negative electrode material includes silicon oxide, lithium titanate, graphite, silicon or hard carbon.
[0009] In some embodiments, the compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.75g / cm 3 , further, 1.83g / cm 3 ≥ρ≥1.0g / cm 3In some embodiments, the thickness h of the active material layer on one side of the current collector satisfies: 1500 μm ≥ h ≥ 13 μm, and further, 150 μm ≥ h ≥ 40 μm, which is beneficial to preventing the negative electrode active material layer from falling off while improving the energy density.
[0010] In some embodiments of the present application, the active material layer includes a conductive agent, and the mass percentage of the conductive agent in the active material layer is 0% to 2% based on the total mass of the active material layer. In some embodiments, the mass percentage of the conductive agent in each region of the active material layer gradually increases with the increase of the spacing distance from the current collector in the thickness direction, thereby improving the conductivity of the active material layer as a whole. In some embodiments, the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black, or conductive carbon black.
[0011] In some embodiments of the present application, the active material layer includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber. In some embodiments, based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 1.0% to 15.8%.
[0012] In some embodiments of the present application, the active material layer includes a polymer compound, and based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 1.6% to 7%.
[0013] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to manufacture any electrode in the present application, comprising: applying a slurry of an active material layer to at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: plasma treating the initial electrode in a vacuum environment, the gas source comprising at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate being 3000sccm to 5000sccm, the temperature being 20°C to 60°C, wherein the plasma power is 3kW to 5kW and the treatment time is 1min to 1.2min, or the plasma power is 0.5kW to 3kW and the treatment time is 1min to 1.2min; or, heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature being greater than 200°C, and the heat treatment time being 5min to 15min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, the laser intensity being 30W to 100W, and the treatment time being 0.3s to 0.5s.
[0014] In some embodiments, processing the initial electrode includes: heat treating the initial electrode in a vacuum or inert gas environment, with a heat treatment temperature of 350°C to 400°C and a heat treatment time of 10 min to 15 min, or a heat treatment temperature of 400°C to 500°C and a heat treatment time of 5 min to 10 min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, with a laser intensity of 30W to 70W and a treatment time of 0.5s, or a laser intensity of 70W to 100W and a treatment time of 0.3s.
[0015] In some embodiments of the present application, an electrochemical device is provided, comprising an electrode; the electrode is any electrode of the present application; or, the electrode is an electrode prepared by the preparation method provided in the present application.
[0016] In some embodiments of the present application, an electronic device is provided, including the electrochemical device provided in the present application.
[0017] An electrode proposed in an embodiment of the present application comprises a current collector and an active material layer located on one side or both sides of the current collector; the active material layer is divided into four detection areas, and the detection areas are subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis show that the mass percentage of weight loss in the detection area from 200°C to 800°C gradually increases with the decrease in the spacing distance between the detection area and the current collector in the thickness direction. In the embodiment of the present application, the active material layer has a low content of polymer compounds in the area close to the electrode surface, thereby increasing the overall conductivity of the active material layer, thereby improving the overall conductivity of the electrode, which is beneficial to increasing the thickness of the electrode, and further beneficial to increasing the capacity and energy density of the electrochemical device using the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and other features, advantages and aspects of the embodiments of the present application will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. Throughout the accompanying drawings, the same or similar reference numerals represent the same or similar elements. It should be understood that the drawings are schematic and that components and elements are not necessarily drawn to scale.
[0019] Figure 1 It is a schematic diagram of an electrode according to an embodiment of the present application. DETAILED DESCRIPTION
[0020] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.
[0021] In order to improve the energy density of electrochemical devices, some technologies increase the energy density of electrochemical devices by increasing the thickness of the active material layer in the electrode. However, increasing the thickness of the active material layer in the electrode may deteriorate the conductivity of the active material layer due to the excessive thickness of the active material layer. In order to improve the conductivity of the active material layer, some technologies use a multi-layer active material layer structure, but the composite cold pressing process of multiple single-layer structures is complicated, and it is impossible to avoid the change of the original compaction density and porosity of each single layer during the cold pressing process again, and the joints between the layers are prone to delamination due to loose bonding, which affects the conduction of electrons and ions and deteriorates the cycle performance. In other technologies, lasers are used to punch holes in the active material layer, but laser drilling is inefficient, costly, and energy density is easily lost during the drilling process. In other technologies, a pore-forming agent solution is applied to the electrode surface, but this cannot avoid the dissolution of the electrode surface, and the depth of the holes formed by the pore-forming agent is limited, which has limited improvement on the near-current collector side. The above technologies solve the problem of ion transport from electrolyte to the surface of active material through different methods, but the ion transport from the surface of active material to the inside of active material layer remains unchanged, the obstacle of ion transport still exists, and the improvement effect is not good.
[0022] Some embodiments of the present application provide an electrode that can improve the conductivity of the active material layer of the electrode, thereby facilitating the improvement of the energy density of the electrochemical device. In some embodiments, an electrode is proposed, which can be an electrode of an electrochemical device, and the electrode includes a current collector and an active material layer located on one side or both sides of the current collector, and the current collector can be copper foil, aluminum foil or steel foil, etc.; along the thickness direction of the active material layer, the active material layer is divided into 4 parts, each part is a detection area, and each detection area is subjected to thermogravimetric analysis at a heating rate of 10°C / min in an inert atmosphere. The results of the thermogravimetric analysis show that the mass percentage of the weight loss of the detection area at 200°C to 800°C gradually increases as the distance between each detection area and the current collector in the thickness direction decreases.
[0023] In conventional technology, the compaction density of the outer layer of the electrode after cold pressing is greater than the compaction density of the inner layer, and during the drying process of the active material layer, the binder and the conductive agent float up, resulting in the electrolyte being difficult to infiltrate, and the binder coating the surface of the active material, and the transmission of ions from the electrolyte to the inside of the active material layer is blocked. Therefore, in some embodiments of the present application, the results of thermogravimetric analysis show that the mass percentage of weight loss in the detection area at 200°C to 800°C gradually increases with the decrease of the spacing distance between the detection area and the current collector in the thickness direction, that is, the mass percentage of weight loss in each detection area changes with the spacing distance between each detection area and the current collector, which indicates that the polymer compound The content gradually decreases or decreases gradually in the direction away from the current collector, reducing the content of the polymer compound in the active material layer near the electrode surface, which can reduce the barrier of the polymer compound to ion transport and reduce the coating of the polymer compound on the active material. By improving the distribution state of the polymer compound in the active material layer, the kinetic properties of the active material layer are improved, thereby improving the overall conductivity of the active material layer for ions and electrons. In this way, when the thickness of the active material layer is increased to increase the energy density of the electrochemical device, the electrical performance of the electrochemical device will not be deteriorated due to the increase in the thickness of the active material layer because the active material layer has good conductivity.
[0024] In some embodiments of the present application, the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the number of weight loss peaks of the active material layer at 200°C to 800°C is greater than or equal to 2. In some embodiments, the number of weight loss peaks greater than or equal to 2 indicates that at least two polymer compounds are present in the active material layer, which may be a binder and / or a thickener.
[0025] In some embodiments, the number of weight loss peaks of the active material layer at 200°C to 350°C is greater than or equal to 1, and the number of weight loss peaks of the active material layer at 350°C to 800°C is greater than or equal to 1, which indicates that the active material layer in the embodiments of the present application has a polymer compound with a low decomposition temperature and a polymer compound with a high decomposition temperature, the low decomposition temperature may be 200°C to 350°C, and the high decomposition temperature may be 350°C to 800°C. The substance corresponding to the weight loss peak at 200°C to 350°C may be a thickener, and the substance corresponding to the weight loss peak at 350°C to 800°C may be a binder.
[0026] In some embodiments of the present application, the weight loss mass percentage of the active material layer at 200° C. to 350° C. is M 1 , 0≤M 1 ≤1.5%, further, 0.1≤M 1 ≤,2.2%, in some embodiments, the weight loss mass percentage of the active material layer at 350°C to 800°C is M 2 , 0≤M2 ≤13%, further, 0.15≤M 2 ≤3.4%.
[0027] In some embodiments of the present application, the electrode is a negative electrode, the current collector can be copper foil, aluminum foil, steel foil, etc., and the compaction density of the active material layer is ρ≥0.6g / cm 3 , a higher compaction density indicates that the mass of the active material layer carried by the electrode per unit volume is greater. The greater the mass of the negative electrode active material layer, the more energy that can be stored per unit volume of the electrochemical device, thereby increasing the energy density. In some embodiments, the compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.75g / cm 3 , which is beneficial to improve the energy density of the electrochemical device. In some embodiments, by limiting the compaction density of the active material layer to not less than 0.75 g / cm 3 The energy density of the electrochemical device can be further guaranteed, while the compaction density of the active material layer is limited to no more than 1.85 g / cm 3 This can prevent the particles in the active material layer from breaking due to excessive compaction density, which increases the consumption of electrolyte and deteriorates the cycle performance. 3 ≥ρ≥1.0g / cm 3 , by further adjusting the compaction density to improve the overall cycling performance and storage performance.
[0028] In some embodiments of the present application, the thickness h of the active material layer on one side of the current collector is ≥ 13 μm. In some embodiments, a thicker active material layer is beneficial to increase the proportion of the active material layer in the electrochemical device, thereby increasing the energy density of the electrochemical device. In some embodiments of the present application, the thickness h of the active material layer on one side of the current collector satisfies: 1500 μm ≥ h ≥ 13 μm. By limiting the minimum thickness of the active material layer, the thickness of the active material layer can be guaranteed, thereby increasing the overall energy density of the electrochemical device. By limiting the thickness of the active material layer to no more than 1500 μm, the problem of separation between the active material layer and the current collector that may occur due to excessive thickness of the active material layer is prevented. In some embodiments, 150 μm ≥ h ≥ 40 μm, thereby further improving the energy density and structural stability of the pole piece.
[0029] In some embodiments of the present application, the porosity n of the active material layer satisfies: 35% ≥ n ≥ 30%. By limiting the porosity of the active material layer to not less than 30%, sufficient infiltration between the active material layer and the electrolyte can be ensured, and sufficient transmission channels can be provided. By limiting the porosity of the active material layer to not more than 35%, adverse effects on the volume energy density can be prevented.
[0030] In some embodiments of the present application, the active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon-based materials, tin-based materials, lithium metal materials or carbon materials. Optionally, the negative electrode material includes at least one of silicon oxide, lithium titanate, graphite, silicon or hard carbon.
[0031] In some embodiments of the present application, the active material layer includes a conductive agent. Based on the total mass of the active material layer, the mass percentage of the conductive agent in the active material layer is 0% to 2%. The mass percentage of the conductive agent can be 0% or 2%. The conductive agent can improve the conductivity of the active material layer.
[0032] In some embodiments of the present application, the mass percentage of the conductive agent in each region of the active material layer gradually increases as the distance between each region and the current collector in the thickness direction increases. In conventional technology, the compaction density of the surface of the active material layer after the electrode is cold pressed is greater than the compaction density inside, resulting in the electrolyte being difficult to infiltrate, and ions being difficult to enter from the surface, affecting the transmission of ions to the current collector. Considering the above problems, in some embodiments of the present application, the distribution state of the conductive agent of the active material layer is adjusted, so that the mass percentage of the conductive agent gradually increases with the increase of the distance between the conductive agent and the current collector in the thickness direction, so that ions can enter the interior of the active material layer from the surface of the active material layer, thereby improving the electronic conduction of the active material layer and improving the electrode kinetics.
[0033] In some embodiments of the present application, the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black or conductive carbon black. The carbon nanotubes in the conductive agent may be single-walled carbon nanotubes or multi-walled carbon nanotubes, which can increase long-range electron conduction.
[0034] In some embodiments of the present application, the active material layer includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber;
[0035] In some embodiments of the present application, the mass percentage of the polymer compound in the active material layer is 1.0% to 15.8%. Too low a mass percentage of the polymer compound may result in insufficient adhesion between the active material layer and the current collector, and too high a mass percentage of the adhesive force may affect the conductivity of the active material layer. In some embodiments, the mass percentage of the polymer compound in the active material layer is 1.6% to 7%.
[0036] In some embodiments of the present application, the polymer compound is distributed in a point-like or surface-like manner on the surface of the active material (e.g., the negative electrode material) of the active material layer, and is concentrated on the surface of the active material or between the particles of the active material. The active material is more exposed, which reduces the coating area of the active material by the polymer compound, reduces the obstacle to the transmission of electrons and ions, and improves the kinetic performance.
[0037] In some embodiments of the present application, the number of weight loss peaks at 200°C to 800°C in the detection area farthest from the current collector in the thickness direction is 0. In some embodiments, the surface of the active material layer away from the current collector does not contain a polymer compound (such as a binder and / or a thickener), thereby improving the dynamic properties of the surface of the active material layer, increasing the contact area with the electrolyte, and facilitating the electrolyte to infiltrate the interior of the active material layer.
[0038] In some embodiments of this application, please refer to Figure 1 The electrode includes a current collector 10 and an active material layer, the active material layer includes an active material 20, a conductive agent 30 and a binder 40, wherein the active material 20 may include a first active material and a second active material, the particle size of the first active material is larger than the particle size of the second active material, and the gap is fully filled by adapting the active materials of different particle sizes. The binder 40 may include a first binder and a second binder, the first binder may be in a point shape, the second binder may be in a chain shape, the first binder and the second binder may be independently selected from styrene acrylate and lithium carboxymethyl cellulose, the active material layer may be divided into a plurality of detection areas along the thickness direction, wherein there may be no binder in the detection area farthest from the current collector along the thickness direction.
[0039] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to prepare any electrode of the present application, comprising: applying a slurry of an active material layer to at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: plasma treating the initial electrode in a vacuum environment, the gas source comprising at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate being 3000sccm to 5000sccm, the temperature being 20°C to 60°C, wherein the plasma power is 3kW to 5kW and the treatment time is 1min to 1.2min, or the plasma power is 0.5kW to 3kW and the treatment time is 1min to 1.2min; or, heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature being greater than 200°C, and the heat treatment time being 5min to 15min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, the laser intensity being 30W to 100W, and the treatment time being 0.3s to 0.5s.
[0040] In some embodiments of the present application, processing the initial electrode may further include: heat treating the initial electrode in a vacuum or inert gas environment, with a heat treatment temperature of 350°C to 400°C and a heat treatment time of 10 min to 15 min, or a heat treatment temperature of 400°C to 500°C and a heat treatment time of 5 min to 10 min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, with a laser intensity of 30W to 70W and a treatment time of 0.5s, or a laser intensity of 70W to 100W and a treatment time of 0.3s.
[0041] In some embodiments of the present application, another method for preparing an electrode is proposed. On at least one side of the current collector, slurry 1 to slurry n are sequentially coated on the current collector in a multilayer coating manner to form an active material layer having multiple sublayers. The active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis show that the mass percentage of weight loss of each sublayer of the active material layer at 200°C to 800°C gradually increases as the spacing distance between the sublayer and the current collector in the thickness direction decreases.
[0042] In some embodiments of the present application, an electrochemical device is provided, comprising an electrode; the electrode is any electrode of the present application; or, the electrode is an electrode prepared by the preparation method provided in the present application.
[0043] In some embodiments of the present application, the electrochemical device includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. In some embodiments, the negative electrode and the positive electrode can be any of the above electrodes. In some embodiments, the current collector of the positive electrode can be Al foil, and of course, other current collectors commonly used in the art can also be used.
[0044] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 50 μm.
[0045] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from alumina (Al 2 O 3 ), silicon oxide (SiO 2 ), magnesium oxide (MgO), titanium oxide (TiO 2 ), hafnium dioxide (HfO 2), tin oxide (SnO 2 ), cerium dioxide (CeO 2 ), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3 ), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece.
[0046] In some embodiments of the present application, the electrochemical device may be wound or stacked. In some embodiments, the positive electrode and / or negative electrode of the electrochemical device may be a multilayer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.
[0047] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiSiF 6 , LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF 6 , because it has high ionic conductivity and can improve the cycle characteristics.
[0048] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0049] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0050] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0051] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0052] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.
[0053] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode, a separator, and a negative electrode are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.
[0054] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.
[0055] The present application proposes an electronic device, including an electrochemical device; the electrochemical device is an electrochemical device of any one of the present application. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera or a large household battery, etc.
[0056] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example, and both the specific embodiments and comparative examples divide the electrode active material layer into four detection areas along the thickness direction, and the thickness of each detection area is 1 / 4 of the total thickness of the active material layer, and the first detection area, the second detection area, the third detection area, and the fourth detection area are gradually spaced from the current collector in the thickness direction. However, the thickness of the active material layer in the four detection areas in the present application can be the same or different.
[0057] Example 1
[0058] Preparation of positive electrode sheet: Mix the positive electrode material lithium cobalt oxide, the polymer compound polyvinylidene fluoride, and the conductive agent conductive carbon black in a mass ratio of 97.5:1.5:1, use N-methylpyrrolidone (NMP) as a solvent, prepare into a slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain the positive electrode sheet.
[0059] Preparation of negative electrode sheets: negative electrode material graphite, polymer compound (styrene acrylate and lithium carboxymethyl cellulose), conductive agent carbon nanotubes, are mixed in a mass ratio of 97:0.5:0.5:2, deionized water is used as solvent, to form a negative electrode active material layer slurry, copper foil is used as the negative electrode collector, the slurry of the negative electrode active material layer is coated on the negative electrode collector, and dried at 90°C. The dried electrode sheet is treated by heat treatment at a temperature of 400°C to 500°C and a heat treatment time of 5min to 10min, and the negative electrode sheet is obtained after heat treatment.
[0060] Preparation of isolation film: The isolation film is 8 μm thick polyethylene (PE).
[0061] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.
[0062] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.
[0063] The relevant parameters of Example 1 are as follows: The compaction density of the active material layer of the negative electrode is 1.75 g / cm 3 The thickness of the active material layer on one side of the negative current collector is 80 μm, the porosity of the negative active material layer is 32%, the negative electrode material is graphite, the type of the negative conductive agent is carbon nanotubes, the polymer compound of the negative electrode is a mixture of styrene acrylate and lithium carboxymethyl cellulose, the mass ratio of the two substances is 1:1, the mass percentage of the polymer compound in the negative active material layer is 1%, the active material layer in the negative electrode includes 4 detection areas with a thickness of 20 μm from the side away from the current collector to the side close to the current collector, which are the first detection area, the second detection area, the third detection area, and the fourth detection area. The mass content of the conductive agent in the first detection area is 2.02%, the mass content of the conductive agent in the second detection area is 2.012%, the mass content of the conductive agent in the third detection area is 2.006%, and the mass content of the conductive agent in the fourth detection area is 2%. At 200°C to 800°C, the conductive agent is 2.012%. The weight analysis shows that the thermogravimetric mass change of the first detection area from 200°C to 350°C is 0%, the thermogravimetric mass change of the first detection area from 350°C to 800°C is 0%, the thermogravimetric mass change of the second detection area from 200°C to 350°C is 0.13%, the thermogravimetric mass change of the second detection area from 350°C to 800°C is 0.19%, the thermogravimetric mass change of the third detection area from 200°C to 350°C is 0.22%, and the thermogravimetric mass change of the third detection area from 350°C to 800°C is 0.22%. The thermogravimetric mass change from 350°C to 800°C is 0.34%, the thermogravimetric mass change from 200°C to 350°C in the 4th detection area is 0.32%, the thermogravimetric mass change from 350°C to 800°C in the 4th detection area is 0.49%, the number of thermogravimetric weight loss peaks of the active material layer of the negative electrode at 200°C to 350°C is 1, the number of thermogravimetric weight loss peaks at 350°C to 800°C is 1, and the number of thermogravimetric weight loss peaks at 200°C to 800°C is 2.
[0064] Other embodiments are based on the steps of embodiment 1 and parameters are changed. The specific changed parameters are shown in the following table.
[0065] The differences between Comparative Examples 1 to 3 and Example 1 are shown in the table below. In none of the comparative examples, the negative electrode active material layer was treated.
[0066] The test methods of the present application are described below.
[0067] 1. Thermogravimetric test
[0068] The thermogravimetric analysis test atmosphere is nitrogen atmosphere, the heating rate is 10℃ / min, the active material layer is divided into 4 parts along the thickness direction, each part is a detection area, and the thermogravimetric test is carried out after the active material layer of the corresponding detection area is peeled off by mechanical means. The test temperature range is 200℃ to 350℃ and 350℃ to 800℃.
[0069] 2. Resistivity test
[0070] The resistivity of the active material layer is tested using a resistance tester. The upper and lower plane controllable pressure probes are used to directly measure the electrode. An alternating current is loaded to the test positive electrode or negative electrode. At the same time, a certain pressure (0.35T) is applied to the test active material layer to obtain the overall resistance in the thickness direction of the electrode. At the same time, the area (A) and thickness (l) of the tested electrode are collected, and the resistivity of the tested electrode is derived according to the resistivity calculation formula (ρ=R*A / l).
[0071] 3. AC resistance test
[0072] A small 1Khz AC current is applied to the positive and negative electrodes of the battery, and the AC resistance of the battery is obtained by measuring the voltage response.
[0073] 4. 25℃ DC resistance DCR test
[0074] At 25°C, charge the lithium-ion battery to 4.45V at 0.5C, then charge to 0.05C at constant voltage; let stand for 30 minutes; discharge at 0.1C for 3 hours until the battery state of charge is 70% SOC (record the corresponding discharge end voltage value U1), and discharge at 1C for 1 second (record the corresponding discharge end voltage value U2). Among them, "1C" is the current value that completely discharges the battery capacity within 1 hour. The DCR of the battery at 70% SOC is calculated according to the following formula: DCR = (U1-U2) / (1C-0.1C).
[0075] 5. Rate performance test
[0076] In an environment of 25℃, the battery was discharged to 3V at a constant current, and the first charge and discharge were performed. Constant current charging was performed at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then constant current discharge was performed at a discharge current of 0.2C until the final voltage was 3V. At this time, the discharge capacity of 0.2C was recorded, and then the battery was repeatedly charged at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then the discharge rate was set to 3C constant current discharge until the final voltage was 3V, and the discharge capacity of 3C was recorded at this time.
[0077] 3C discharge capacity retention rate = (3C discharge capacity / 0.2C discharge capacity) × 100%
[0078] Table 1
[0079]
[0080]
[0081] Table 2
[0082]
[0083]
[0084] Note: CNT is carbon nanotube. The preparation parameters of Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1, and the performance test results are shown in Table 2. The active material layer in the application form is the active material layer of the negative electrode. The parameters not shown in the Examples and Comparative Examples in Table 1 are the same as those in Example 1. The number of thermogravimetric weight loss peaks of the active material layer of the Examples and Comparative Examples in Table 1 at 200°C to 350°C is 1, the number of thermogravimetric weight loss peaks at 350°C to 800°C is 1, and the number of thermogravimetric weight loss peaks at 200°C to 800°C is 2.
[0085] As shown in Table 2, in Examples 1 to 8, the mass percentage of weight loss in the detection area at 200°C to 350°C and the mass percentage of weight loss at 350°C to 800°C gradually increase as the distance between the detection area and the current collector in the thickness direction decreases. In Comparative Examples 1 to 3, the mass percentage of weight loss in the detection area at 200°C to 350°C and 350°C to 800°C remains unchanged with the distance between the detection area and the current collector in the thickness direction. The AC resistance and DC resistance of Examples 1 to 8 are significantly lower than those of Comparative Examples 1 to 3, and the 3C discharge capacity retention rate of Examples 1 to 8 is higher than that of Comparative Examples 1 to 3. It can be seen that when the mass percentage of weight loss in the detection area of the active material layer at 200°C to 800°C gradually increases as the distance between the detection area and the current collector in the thickness direction decreases, the kinetic performance of the lithium ion battery can be improved, the rate discharge performance of the lithium ion battery can be improved, and the energy density of the lithium ion battery can be improved.
[0086] Please continue to refer to Table 1 and Table 2. It can also be seen from Examples 1 to 8 that when the mass change in the detection area from 200°C to 350°C is 0% to 1.5%, and when the mass change in the detection area from 350°C to 800°C is in the range of 0% to 13%, the lithium-ion batteries have good conductivity and rate performance. This may be because the mass change during the thermogravimetric analysis process is related to the content of polymer substances. The greater the mass change, the greater the content of polymer substances. Therefore, when the mass change during the thermogravimetric analysis process is small, it indicates that the active material layer contains less polymer substances, which is beneficial to improving ion and electron conduction and improving kinetic performance.
[0087] It can also be seen from Tables 1 and 2 that good results can be achieved by heat treatment, laser bombardment or plasma treatment of the negative electrode active material layer. Regardless of whether heat treatment or multi-layer coating is used, as long as the mass percentage of weight loss in the detection area from 200°C to 800°C gradually increases with the direction approaching the current collector, the effect of improving the kinetic performance and improving the cycle performance in the present application can be achieved.
[0088] Table 3
[0089]
[0090] The preparation parameters and test results of Examples 9 to 16 and Example 3 are shown in Table 3. The difference between Examples 9 to 16 and Example 3 is only the data shown in Table 3, and the other data not shown are the same.
[0091] It can be seen from Examples 9 to 12 and 3 that as the compaction density of the negative electrode active material layer increases, the negative electrode porosity decreases accordingly, the DC resistance and AC resistance gradually decrease, but the 3C discharge capacity retention rate also decreases. This may be because the reduction in porosity shortens the ion transmission path, but the increase in compaction density causes the negative electrode material particles to break and reduces the particle size of the negative electrode material. The reduction in the particle size of the negative electrode material will lead to a decrease in cycle performance. If the compaction density is too small, the negative electrode volume energy density will be insufficient.
[0092] It can be seen from Examples 13 to 16 and 3 that as the thickness of the negative electrode active material layer increases, the AC resistance and the DC resistance increase, and the 3C discharge capacity retention rate decreases. This is because the increase in the thickness of the negative electrode active material layer leads to an increase in the ion transmission path, which in turn leads to an increase in resistance and deteriorates the kinetic performance. If the thickness of the negative electrode active material layer is too small, the negative electrode will be able to store too little energy, which will lead to insufficient capacity of the lithium-ion battery.
[0093] Table 4
[0094]
[0095] The preparation parameters and performance test results of Examples 17 to 20 and 3 are shown in Table 4. The remaining parameters of Examples 17 to 20 not shown are the same as those of Example 3.
[0096] As shown in Table 4, when the negative electrode material is selected from silicon dioxide, lithium titanate, graphite, silicon or hard carbon, it has lower AC resistance and DC electrons and higher 3C discharge capacity retention rate. The performance is best when the negative electrode material is graphite or hard carbon.
[0097] Table 5
[0098]
[0099] The only difference between the parameters of Examples 21 to 25 and Example 3 is the data shown in Table 5. The other parameters of Examples 21 to 25 not shown are the same as those of Example 3. The active material layer in Table 5 is a negative electrode active material layer.
[0100] As shown in Examples 39 to 44, when the conductive agent is conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon fiber, the performance of the lithium-ion battery is good. When the conductive agent is carbon nanotubes or graphene, the AC resistance and DC resistance are low, and the 3C discharge capacity retention rate is the highest. This may be because carbon nanotubes increase the long-range conductivity, and graphene can fill the gaps between the negative electrode materials well to increase the conductivity.
[0101] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrode, characterized in that: The electrode comprises a current collector and an active material layer located on one side or both sides of the current collector; The active material layer is divided into four parts along the thickness direction of the active material layer, each part being a detection area, and the detection area is subjected to thermogravimetric analysis at a heating rate of 10° C. / min under an inert atmosphere, and the result of the thermogravimetric analysis shows that the weight loss mass percentage of the detection area at 200° C. to 800° C. gradually increases as the spacing distance between the detection area and the current collector in the thickness direction decreases; The number of weight loss peaks of the detection area farthest from the current collector in the thickness direction from 200°C to 800°C is zero.
2. The electrode according to claim 1, characterized in that The active material layer is subjected to thermogravimetric analysis at a heating rate of 10° C. / min under an inert atmosphere. The result of the thermogravimetric analysis shows that the number of weight loss peaks of the active material layer at 200° C. to 800° C. is greater than or equal to 2.
3. The electrode according to claim 2, characterized in that The number of weight loss peaks of the active material layer at 200° C. to 350° C. is greater than or equal to 1, and the number of weight loss peaks of the active material layer at 350° C. to 800° C. is greater than or equal to 1.
4. The electrode according to claim 3, characterized in that Satisfy at least one of the following: (a) the weight loss mass percentage of the active material layer at 200° C. to 350° C. is M1, 0≤M1≤2.2%; (b) The weight loss mass percentage of the active material layer at 350° C. to 800° C. is M2, and 0≤M2≤13%.
5. The electrode according to claim 3, characterized in that Satisfy at least one of the following: (c) the weight loss mass percentage of the active material layer at 200° C. to 350° C. is M1, 0.1≤M1≤1.5%; (d) The mass percentage of weight loss of the active material layer at 350° C. to 800° C. is M2, and 0.15≤M2≤3.4%.
6. The electrode according to claim 1, characterized in that The electrode is a negative electrode.
7. The electrode according to claim 6, characterized in that The electrode satisfies at least one of the following: (e) The compaction density of the active material layer is ρ≥0.6 g / cm 3 ; (f) the thickness of the active material layer on one side of the current collector is h≥13 μm; (g) the porosity n of the active material layer satisfies: 35% ≥ n ≥ 30%; (h) The active material layer includes a negative electrode material, and the negative electrode material includes at least one of silicon oxide, lithium titanate, graphite, silicon or hard carbon.
8. The electrode according to claim 6, characterized in that The electrode satisfies at least one of the following: (i) The compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.75 g / cm 3 ; (j) The thickness h of the active material layer on one side of the current collector satisfies: 1500 μm ≥ h ≥ 13 μm.
9. The electrode according to claim 6, characterized in that The electrode satisfies at least one of the following: (k) The compaction density ρ of the active material layer satisfies: 1.83 g / cm 3 ≥ρ≥1.0 g / cm 3 ; (l) The thickness h of the active material layer on one side of the current collector satisfies: 150 μm ≥ h ≥ 40 μm.
10. The electrode according to claim 1, characterized in that The active material layer includes a conductive agent and satisfies at least one of the following conditions: (m) based on the total mass of the active material layer, the mass percentage of the conductive agent in the active material layer is 0% to 2%; (n) the mass percentage of the conductive agent in each region of the active material layer gradually increases as the distance between each region and the current collector in the thickness direction increases; (o) The conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene or Ketjen black.
11. The electrode according to claim 1, characterized in that The active material layer includes a polymer compound and satisfies at least one of the following conditions: (p) the polymer compound comprises at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone or styrene acrylate; (q) Based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 1.0% to 15.8%.
12. The electrode according to claim 1, characterized in that The active material layer includes a polymer compound, and based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 1.6% to 7%.
13. A method for preparing an electrode according to any one of claims 1 to 12, characterized in that: include: Applying the slurry of the active material layer to at least one surface of the current collector, drying, and cold pressing to obtain an initial electrode; Processing the initial electrode to obtain the electrode; Wherein, processing the initial electrode comprises: Plasma treatment is performed on the initial electrode under a vacuum environment, the gas source includes at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000 sccm to 5000 sccm, the temperature is 20° C. to 60° C., wherein the plasma power is 3 kW to 5 kW and the treatment time is 1 min to 1.2 min, or the plasma power is 0.5 kW to 3 kW and the treatment time is 1 min to 1.2 min; or, The initial electrode is laser bombarded in a vacuum or inert gas environment, with a laser intensity of 30W to 100W and a processing time of 0.3s to 0.5s.
14. The method for preparing an electrode according to claim 13, characterized in that: Processing the initial electrode includes: The initial electrode is laser-bombarded in a vacuum or inert gas environment, with a laser intensity of 30 W to 70 W and a treatment time of 0.5 s, or a laser intensity of 70 W to 100 W and a treatment time of 0.3 s.
15. An electrochemical device, characterized in that: including electrodes; The electrode is the electrode according to any one of claims 1 to 12; or, The electrode is an electrode prepared by the preparation method described in any one of claims 13 to 14.
16. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 15.
Citation Information
Patent Citations
Making method of lithium ion battery anode sheet
CN103178241A